Analisis Kualitas Pelayanan Publik terhadap Kepuasan Klaim Santunan pada PT Jasa Raharja (Persero) Cabang Kalimantan Selatan - Aldinor Aldinor; Padli Padli; Riswan Yunida (BIMA: Jurnal Bisnis dan Manajemen, 2023)
This research was conducted at PT. Jasa Raharja (Persero) South Kalimantan Branch which is located at Jalan A.Yani Km 4.5, No.35, Flower Garden, East Banjarmasin District, Banjarmasin City, South Kalimantan Province 70325 is a company engaged in social insurance owned by (BUMN). This research aims to find out how much influence the quality of public services has on the satisfaction of compensation claims at PT. Jasa Raharja (Persero) South Kalimantan Branch (1) This research method uses a quantitative method with the help of SPSS statistic software version 26. Data collection techniques use questionnaires that are distributed to compensation claims of PT. Jasa Raharja (Persero) South Kalimantan Branch as a sample of 20 people with a sampling technique, namely purposive sampling. While the data analysis technique used is simple linear regression (2) The results showed that there was a positive and significant influence between the quality of public services and the satisfaction of compensation claims(3)This can be seen from the result of the equation Y =30,897+0,672X. The significant level of public service quality is 0,000 less than 0.005 with a value of t count > t table (2,033 > 1.325324). while the determination coefficient of R Square is 0.205 or 20.5% which means that there are 80.5% of other variables that influence the purchase decision.